PENGARUH UPACARA BENDERA TERHADAP RASA NASIONALISME SISWA SMAN 2 MUARO JAMBI - Absyari, Absyari; Agustiningsih, Nur; yanto, Ferry (Universitas Batanghari Jambi, 2024)
This research and development aims to find out and obtain data on the students' knowledge of the flag ceremony against the nationalism attitude of students at SMA N 2 Muraro Jambi. This research used correlational method, which is to determine whether or not there is a relationship between two or more variables and how many degrees of relationship there are. The data collection technique uses questionnaire instruments. The research sample amounted to 165 students. Data analysis is quantitative/statistical with the aim of testing the hypothesis that has been established. The results of the study showed that the implementation of the flag ceremony had an effect on the attitude of nationalism of students of SMA Negeri 2 Muaro Jambi. The attitude of nationalism of students at SMA Negeri 2 Muaro Jambi mostly shows a fairly good attitude. Based on statistical tests using regression analysis of the two variables, there is a positive or unidirectional relationship. So the better the level of the Flag Ceremony, the higher the attitude of Nationalism at SMA Negeri 2 Muaro Jambi